Exosome‐mediated delivery of miR‐204‐5p inhibits tumor growth and chemoresistance. (2nd July 2020) - Yao, Surui; Yin, Yuan; Jin, Guoying; Li, Dan; Li, Min; Hu, Yaling; Feng, Yuyang; Liu, Yuhang; Bian, Zehua; Wang, Xue; Mao, Yong; Zhang, Jia; et al.
Abstract: Background: Nano‐sized extracellular vesicles secreted by cells play key roles in intercellular crosstalk, and appear to be an excellent biocompatible material as therapeutic cargoes in vivo. Previously, we have demonstrated that miR‐204‐5p is a key tumor suppressor that could inhibit tumor growth, metastasis and chemoresistance. Methods: A HEK293T cell line stably expressing miR‐204‐5p (293T‐miR‐204) was constructed by lentivirus transduction. Fluorescence real‐time quantitative PCR (qPCR) was applied to measure the expression of miR‐204‐5p. CCK‐8 and colony formation assays were used to evaluate the in vitro anticancer effects, and the flow cytometry was used to detect apoptosis. The in vivo therapeutic effects of exosomal miR‐204‐5p were evaluated using a xenograft mouse model. Western blots were used to detect the protein levels of CD63, Flotillin‐2, RAB22A and Bcl2. The protein levels of RAB22A and Bcl2 in tumor tissues were measured by immunohistochemistry staining. Results: MiR‐204‐5p was clearly upregulated in CRC cells after coculturing with 293T‐miR‐204 cell‐derived conditioned medium (CM) or exosomes. CCK‐8 and colony formation assays showed that the cell proliferation ability of CRC cells was clearly inhibited by 293T‐miR‐204 cell‐derived CM or exosomes. The inhibitory effects of exosomal miR‐204‐5p on cell proliferation were further confirmed in other types of cancers. Exosomal miR‐204‐5p could induce apoptosis and increase the sensitivity of cancer cells to the chemotherapeutic drug—5‐fluorourcil. In addition, exosomal miR‐204‐5p inhibited the tumor growth in mice. Western blot assay and IHC staining showed that the protein levels of miR‐204‐5p targets were clearly decreased in cancer cells or xenograft tissues treated with exosomal miR‐204‐5p. Conclusions: In this study, we confirmed that exosomal miR‐204‐5p could efficiently inhibit cancer cell proliferation, induce apoptosis and increase chemosensitivity by specifically suppressing the target genes of miR‐204‐5p in human cancer cells. Abstract : In this study, we confirmed that exosomal miR‐204‐5p could efficiently inhibit cancer cell proliferation, induce apoptosis, and increase chemosensitivity by specifically suppressing the target genes of miR‐204‐5p in human cancer cells.